2021
DOI: 10.1111/jvim.16315
|View full text |Cite
|
Sign up to set email alerts
|

The use of high‐dose immunoglobulin M‐enriched human immunoglobulin in dogs with immune‐mediated hemolytic anemia

Abstract: Background The IV use of human immunoglobulin (hIVIG) in dogs with primary immune‐mediated hemolytic anemia (IMHA) has been described previously, but herein we describe the use of high‐dose IgM‐enriched hIVIG (Pentaglobin). Hypothesis/Objectives Dogs treated with high‐dose Pentaglobin will experience shorter time to remission and hospital discharge and have decreased transfusion requirements compared to dogs receiving standard treatment alone. Animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…All of the patients that did not survive in this study were humanely euthanized due to ongoing blood transfusion requirements and the financial limitation of continuing treatment. Our results agreed with those of Bestwick et al, 7 which demonstrated no benefit in using an Menriched human immunoglobulin, Pentaglobin, in early treatment for patients with primary IMHA. That study 7 administered hIVIG at a dose of 1 g/kg, a higher dose than the present study, and instituted therapy in an early stage of the disease.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…All of the patients that did not survive in this study were humanely euthanized due to ongoing blood transfusion requirements and the financial limitation of continuing treatment. Our results agreed with those of Bestwick et al, 7 which demonstrated no benefit in using an Menriched human immunoglobulin, Pentaglobin, in early treatment for patients with primary IMHA. That study 7 administered hIVIG at a dose of 1 g/kg, a higher dose than the present study, and instituted therapy in an early stage of the disease.…”
Section: Discussionsupporting
confidence: 92%
“…This study found no specific benefit of such use in the early treatment and response of dogs with IMHA compared to prednisolone alone. 7 Use in ITP has been investigated with a particular interest in reporting platelet recovery times compared to vincristine administration. Most studies found no significant difference between the administration of vincristine versus hIVIG, with the conclusion that vincristine is superior to IVIG in terms of cost, ease of administration, and reduced risk of adverse events.…”
Section: Clinical Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…Time to PCV stabilization was defined as the number of days until the PCV plateaued (±2%) for a period of ≥24 hours, followed by a static or increasing PCV and lack of requirement for additional blood transfusions. 12 Duration of hospitalization was calculated from the day of hospital admittance to the day of hospital discharge. Dogs were considered to have a “relapse” of na‐IMHA when the dog represented to a veterinarian with clinicopathologic changes consistent with suspected or definitive na‐IMHA based on the ACVIM consensus statement, in addition to a reduction in PCV, at a period greater than 2 weeks after the initial diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…Immunosuppressive effectiveness was determined based on 4 criteria: (a) time to PCV stabilization, (b) duration of hospitalization, (c) disease relapse, and (d) mortality. Time to PCV stabilization was defined as the number of days until the PCV plateaued (±2%) for a period of ≥24 hours, followed by a static or increasing PCV and lack of requirement for additional blood transfusions 12 . Duration of hospitalization was calculated from the day of hospital admittance to the day of hospital discharge.…”
Section: Methodsmentioning
confidence: 99%